Ab initio method of optical investigations of CdS1−xTex alloys under quantum dots diameter effect. (May 2015) - Al-Douri, Y.; Hashim, U.; Khenata, R.; Reshak, A.H.; Ameri, M.; Bouhemadou, A.; Rahim Ruslinda, A.; Md Arshad, M.K.
Highlights: Study and validate the recent quantum dot potential model of CdS1−x Te x alloys using ab initio method. Analysis optical properties of QD's CdS1−x Te x alloys. Investigate refractive index and optical dielectric constant of QD's CdS1−x Te x alloys. Search the appropriate QD's diameter for high technological applications of solar cells. Abstract: The indirect energy gap ( Γ − X ) is calculated using density functional theory (DFT) of the full potential-linearized augmented plane wave (FP-LAPW) method as implemented in WIEN2K code. The Engel–Vosko generalized gradient approximation (EV-GGA) formalism is used to optimize the corresponding potential for energetic transition and optical properties calculations of CdS1− x Te x alloys as a function of quantum dot diameter and is used to test the validity of our model of quantum dot potential. The refractive index and optical dielectric constant are investigated to explore best applications for solar cells.